Familism Values, Family Time, and Mexican‐Origin Young Adults' Depressive Symptoms. Issue 1 (14th September 2015) - Zeiders, Katharine H.; Updegraff, Kimberly A.; Umaña‐Taylor, Adriana J.; McHale, Susan M.; Padilla, Jenny
Abstract : Using longitudinal data across eight years, this study examined how parents' familism values in early adolescence predicted youths' depressive symptoms in young adulthood via youths' familism values and family time. We examined these processes among 246 Mexican‐origin families using interview and phone‐diary data. Findings revealed that fathers' familism values predicted male and female youths' familism values in middle adolescence. For female youth only, fathers' familism values also predicted youths' family time in late adolescence. The link between family time and young adults' depressive symptoms depended on parental acceptance and adolescent gender: Among female and male youth, family time predicted fewer depressive symptoms, but only when paternal acceptance was high. For female adolescents only, family time predicted fewer depressive symptoms when maternal acceptance was high but more depressive symptoms when maternal acceptance was low. Findings highlight family dynamics as the mechanisms through which familism values have implications for youths' adjustment.